DUKUNGAN KELUARGA DALAM PENCEGAHAN PERGAULAN BEBAS PADA REMAJA DI DESA JAMBU KECAMATAN KAYEN KIDUL KABUPATEN KEDIRI - Sulistyorini, Ariani; Nur Amelia Asrory, Putri (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Promiscuity is a form of deviant behavior that crosses societal norms' boundaries. Adolescents often engage in promiscuity because adolescence is a transition period from childhood to adulthood. Promiscuity can be prevented with family support in the form of attitudes, actions, and acceptance of the family towards its members by always being ready to help and care for them in the form of emotional, appreciative, instrumental, and informational support. The research aims to determine family support in preventing promiscuity in adolescents. In quantitative descriptive research design, the research population is all families with teenage children in Jambu Village totaling 785 families, a sample of 89 respondents using a purposive sampling technique. The research was carried out on March 26 - April 30 2024 in Jambu Village, Kayen Kidul District, Kediri Regency, with a single variable: family support in preventing promiscuity. Questionnaire research instrument, data is analyzed using percentages and interpreted quantitatively. The results of the research were from 89 respondents, the majority of respondents had good support, 70 respondents (79%), a small portion had sufficient support, 17 respondents (19%) and a small portion had poor support, 2 respondents (2%). Family support is influenced by several factors, namely age, gender, education, employment, ever receiving information about promiscuity, sources of information, and the respondent's relationship with teenagers. It is hoped that families with good support will maintain adequate family support and more or less increase their support and that the Village Government will provide education to families and teenagers on how to prevent promiscuity.